2009
DOI: 10.1128/aem.01151-09
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Molecular Tools for Genetic Manipulation of the Pleuromutilin-Producing FungusClitopilus passeckerianus

Abstract: We describe efficient polyethylene glycol (PEG)-mediated and Agrobacterium-mediated transformation systems for a pharmaceutically important basidiomycete fungus, Clitopilus passeckerianus, which produces pleuromutilin, a diterpene antibiotic. Three dominant selectable marker systems based on hygromycin, phleomycin, and carboxin selection were used to study the feasibility of PEG-mediated transformation of C. passeckerianus. The PEG-mediated transformation of C. passeckerianus protoplasts was successful and gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
54
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 56 publications
(85 reference statements)
5
54
0
1
Order By: Relevance
“…Error bars indicate standard deviation studies have reported that multiple integrations predominate in T-DNA transfer to filamentous fungi (Micosh et al 2001). However, similar results to those obtained in our analysis have been reported in Clitopilus passeckerianus (Kilaru et al 2009) and Venturia inaequalis (Fitzgerald et al 2003), where a majority of transformants contained a single copy of T-DNA in the genome. Therefore, the genetic manipulation of H. mompa may be possible because A. tumefaciens transformation resulted in singlecopy integration.…”
Section: Analysis Of Transformantssupporting
confidence: 88%
“…Error bars indicate standard deviation studies have reported that multiple integrations predominate in T-DNA transfer to filamentous fungi (Micosh et al 2001). However, similar results to those obtained in our analysis have been reported in Clitopilus passeckerianus (Kilaru et al 2009) and Venturia inaequalis (Fitzgerald et al 2003), where a majority of transformants contained a single copy of T-DNA in the genome. Therefore, the genetic manipulation of H. mompa may be possible because A. tumefaciens transformation resulted in singlecopy integration.…”
Section: Analysis Of Transformantssupporting
confidence: 88%
“…A. tumefaciens-mediated transformation of G. lucidum protoplasts with plasmid pCAMBIA1301 also failed to achieve hygromycin resistance transformants (data not shown), possibly because the constructs containing the heterologous gene may not be functional in G. lucidum. Previous studies reported that the hygromycin resistance gene and phleomycin resistance gene cannot work in the basidiomycetes Schizophyllum commune and Clitopilus passeckerianus unless the appropriate N terminus and appropriate introns were present within the coding sequences (14,30). In the present study, a homologous selection marker gene cbx r was developed and used to transform basidiomycete by ATMT to establish a stable transformation system for G. lucidum.…”
Section: Discussionmentioning
confidence: 99%
“…The availability of practical transformation systems is a limiting factor for the genetic improvement of basidiomycetous mushrooms for biotechnological applications (11,12,14). Basidiomycete mushrooms generally exhibit higher resistance to genetic transformation compared to ascomycetous fungi (37).…”
mentioning
confidence: 99%
“…eGFP was not expressed in transformants, likely due to the absence of an intron from the 5Ј end of eGFP in pBGgHg, which has been shown to bring about eGFP expression in other basidiomycetes (10,26). The methods and results are presented only for hph.…”
mentioning
confidence: 99%